Enriching Cognizance at the Tertiary Level Students During Transition - Jeyagowri, K.; Abilasha, R.; Ilankumaran, M. (International Journal of Engineering and Technology, 2018)
English language, as a global lingua franca, has its own respect and importance throughout the world. It is considered to be the shrine of knowledge. It is significant to acquire the English language proficiency, to be placed in good jobs. Though every college gives prime importance to English language, unfortunately most of the students fail to acquire good command over the language. In certain cases, students have the poor ability to comprehend learning at the college level because of their different educational background or capability. There are certain hurdles that affect the students from learning the language. Cognizance is an important component of the tertiary level students. Enriching cognizance of students refers to how the learners develop their knowledge in order to get a better idea of learning, awareness of the language skills they notice, and the observation of language learning. The objective of cognizance is to provide more knowledge to students. It promotes self-motivation of the students and enhances their basic skills of learning. Cognitive skill develops the student’s learning skills, notice, recollection and thoughts. This article deals with how cognizance in language learning is developed and thereby to sharpen their skills of learning. Furthermore, this paper analyses the causes and effects of the students’ transitional dilemma at the tertiary level in acquiring language efficacy. It offers some ideas and results based on the problems among the students in attaining the fluency in communication through developing cognition skills. Moreover, the study proposes to help the students to achieve the objective of education.